Investigating the development of entrepreneurial behavior among nascent digital entrepreneurs - Susetyo Darmanto; Adi Ekopriyono; Hikmah; Andalan Tri Ratnawati (Cogent Business & Management, 2023)
This study aims to determine the antecedents of digital entrepreneurial behavior based on the mediating role of self-efficacy in mediating risk propensity, digital knowledge, digital competence, and nascent digital entrepreneurs. The population comprises nascent digital entrepreneurs who previously participated in an entrepreneurial skills program in digital technology field to gain digital competence and received digital start-up funds in Central Java (2020). Seventy participants were elected using purposive random sampling. Composite PLS and structural models were used to test the statistical significance of the paths of the coefficients of the six hypotheses. The results showed that risk propensity, digital entrepreneurial knowledge, and digital competence could encourage participants to strengthen their skills during digital courses to increase their belief in realizing digital business. This study highlights the success of digital entrepreneurial self-efficacy as a mediator of digital entrepreneurial behavior. However, despite the positive effect, the effect of risk propensity on digital entrepreneurial behavior was insignificant. The findings concluded that digital entrepreneurial courses promote digital entrepreneurial behavior, and the government requests that nascent digital entrepreneurs focus on the competence of digital courses to encourage the fourth industrial revolution.
Keywords: 650; digital competence; digital entrepreneurial behavior; digital entrepreneurial knowledge; digital entrepreneurial self-efficacy; risk propensity